PENGARUH GAME SUSUN HURUF TERHADAP PEMEROLEHAN KOSAKATA ANAK USIA 8 TAHUN DI DESA BATU MBULAN SATU KECAMATAN BABUSSALAM KABUPATEN ACEH TENGGARA - Alimatussadiyah Alimatussadiyah; M. Supratman; Irfan Johari (STKIP USMAN SAFRI KUTACANE, 2022)
Department of Indonesian Language and Literature, Usman Safri Kutacane School of Teacher Training and Education. Supervised by Mr. M. Supratman, S, Pd., M.Pd. And Mr. Irfan Johari, S.Pd., M.Pd. This research is an experimental study in the form of Pre-Test and Post-Test which aims to determine the effect of the letter stacking game on the vocabulary acquisition of 8 year old children in Batumbulan Satu Village, Babussalam District, Southeast Aceh Regency through the use of letter stacking games. Data collection techniques used descriptive and inferential statistical analysis. The results of this study prove that whether there is an effect of the word stacking game on the vocabulary acquisition of 8 year old children in Batumbulan Satu Village, Babussalam District, Southeast Aceh Regency through the use of letter stacking games are 1). The results of learning vocabulary for children aged 8 years in Batumbulan Satu Village, Babussalam District, Southeast Aceh Regency after implementing word stacking games have an effect on children's vocabulary acquisition skills which can be seen from the pre-test and post-test results, which are very high 45%, high 45%, moderate 10%, low 0%, and very low at 0% percentage 2). The application of the letter stacking game affects the reading ability of 8-year-old children in Batumbulan Satu Village, Babussalam District, Southeast Aceh Regency after obtaining t_count 6, 705 and t_table 5, 746 then obtained = t_count > t_table or 6>5. So, this research proves that there is an effect of letter stacking games on the vocabulary acquisition of 8 year old children in Batumbulan Satu Village, Babussalam District, Southeast Aceh Regency.